Середньовічна слов'янська гімнографія: бібліографічний огляд - Джиджора, Є. (Слово і Час, 2018)
У статті стверджується, що гімнографія – один із найбільш поширених і репрезентативних
жанрів середньовічної літератури, який уже понад півтора сторіччя є об'єктом наукових студій.
Помічені два умовні періоди: ранній (1860 – 1970-ті роки), пізній (1970-ті роки – до наших днів).
У ранній період текстологи передусім прагнули надрукувати окремі гімнографічні твори та збірки,
супроводжуючи видання палеографічною характеристикою досліджуваних рукописів. У пізній
період текстологічних студій науковці здійснюють історико-типологічний опис гімнографічних
об'єктів, і серед них не лише твори або збірки, а й постаті гімнографів та навіть окремі пісенні
жанри. Водночас в означений період триває видання творів за стародавніми рукописами. The article argues that the leading direction in the study of medieval Slavic hymnographic works
is a textual analysis. In the textology of the Christian hymnography two conditional periods are
distinguished: the early (the 60s of the 19th cent. — 70s of the 20th cent.) and the late (the 70s of
the 20th cent. to nowadays). It is also underlined that in the early period the textologists, above all,
aimed to publish separate works and collections of hymnography with paleographic description of the studied manuscripts. The first part of the article examines the early period, represented by two research trends: publication of the records and description, historical and typological, of particular hymnographic objects. In the late period of the textological studies the scholars perform the historic typological description of the hymnographic objects which include not only separate pieces and collections but also hymnography authors’ images and even separate singing genres. The first textological studies are reduced to publication of the texts with all their differences, the paleographic-textual commentary to the texts, the search of the compositional signs of the works’ usage and the solution of authorship issues. Besides, a range of ancient manuscripts were published at that time as well. В статье утверждается, что гимнография – один из
наиболее распространенных и репрезентативных жанров средневековой литературы, который уже
более полутора столетий выступает объектом научных исследований. Отмечены два условных
периода: ранний (1860 – 1970 гг.) и поздний (1970 гг. – до наших дней). В ранний период текстологи
стремились прежде всего опубликовать отдельные гимнографические произведения и сборники,
сопровождая издания палеографической характеристикой исследуемых рукописей.
В поздний период текстологических студий ученые предпринимают историко-типологическое
описание гимнографических объектов, среди которых не только произведения или сборники,
но и личности гимнографов и даже отдельные песенные жанры. В то же время в указанный
период продолжаются издания произведений по древним рукописям.